Ros Based Slam Implementation for Speech Recognition Autonomous Navigation Dim Sum Trolley - Low, Sin Yee; Abdul Rahman, Hisyam (Evolution in Electrical and Electronic Engineering, 2024)
The Dim Sum Trolley is commonly used in restaurants or tea pavilions to serve dishes. However, a large amount of manpower is needed to push the trolley as well as serve the food. Therefore, an artificial intelligence or portable food trolley has been proposed, in which the food trolley can move autonomously according to voice commands and input commands from the touchpad. The goal of this project is to design and develop an autonomous Dim Sum trolley based on ROS and Gazebo, and the scope of the project can be divided into three scopes: URDF-customized robot, software development using ROS (Robot Operating System), and Gazebo simulator software. This project is conducted fully in simulation with SLAM technology and the ROS operating system, with the URDF robot first being drawn in Fusion 360 and imported into Gazebo software. After that, all the commands and instructions are given to the robots in the gazebo to execute the tasks. From this result of the robot’s location, we can observe that the robot can perform according to the commands given. To conclude, the URDF robot can run perfectly with speech recognition; however, some additional improvements can be made for future work, such as integrating temperature monitoring capabilities into the AI robot to ensure food quality and safety.